Mosquito-disseminated pyriproxyfen yields high breeding-site coverage and boosts juvenile mosquito mortality at the neighborhood scale. - Fernando Abad-Franch; Elvira Zamora-Perea; Gonçalo Ferraz; Samael D Padilla-Torres; Sérgio L B Luz (Public Library of Science (PLoS), 2015)
BACKGROUND:Mosquito-borne pathogens pose major public health challenges worldwide. With vaccines or effective drugs still unavailable for most such pathogens, disease prevention heavily relies on vector control. To date, however, mosquito control has proven difficult, with low breeding-site coverage during control campaigns identified as a major drawback. A novel tactic exploits the egg-laying behavior of mosquitoes to have them disseminate tiny particles of a potent larvicide, pyriproxyfen (PPF), from resting to breeding sites, thus improving coverage. This approach has yielded promising results at small spatial scales, but its wider applicability remains unclear. METHODOLOGY/PRINCIPAL FINDINGS:We conducted a four-month trial within a 20-month study to investigate mosquito-driven dissemination of PPF dust-particles from 100 'dissemination stations' (DSs) deployed in a 7-ha sub-area to surveillance dwellings and sentinel breeding sites (SBSs) distributed over an urban neighborhood of about 50 ha. We assessed the impact of the trial by measuring juvenile mosquito mortality and adult mosquito emergence in each SBS-month. Using data from 1,075 dwelling-months, 2,988 SBS-months, and 29,922 individual mosquitoes, we show that mosquito-disseminated PPF yielded high coverage of dwellings (up to 100%) and SBSs (up to 94.3%). Juvenile mosquito mortality in SBSs (about 4% at baseline) increased by over one order of magnitude during PPF dissemination (about 75%). This led to a >10-fold decrease of adult mosquito emergence from SBSs, from approximately 1,000-3,000 adults/month before to about 100 adults/month during PPF dissemination. CONCLUSIONS/SIGNIFICANCE:By expanding breeding-site coverage and boosting juvenile mosquito mortality, a strategy based on mosquito-disseminated PPF has potential to substantially enhance mosquito control. Sharp declines in adult mosquito emergence can lower vector/host ratios, reducing the risk of disease outbreaks. This approach is a very promising complement to current and novel mosquito control strategies; it will probably be especially relevant for the control of urban disease vectors, such as Aedes and Culex species, that often cause large epidemics.